2019
DOI: 10.1038/s41536-019-0082-7
|View full text |Cite
|
Sign up to set email alerts
|

Trends in clinical trials for stroke by cell therapy: data mining ClinicalTrials.gov and the ICTRP portal site

Abstract: Definitive treatment of stroke constitutes an important thesis of regenerative medicine in the cerebrovascular field. However, to date, no cell therapy products for stroke are yet on the market. In this study, we examined the clinical research trends related to cell therapy products in the stroke field based on data obtained from the ClinicalTrials.gov website and International Clinical Trials Research Platform (ICTRP) portal site. These data do not offer results of clinical trials comprehensively but provide … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 24 publications
0
12
0
Order By: Relevance
“…ClinicalTrials.gov data mining has been used to analyze the characteristics of oncology clinical trials [ 8 ], trends in clinical trials for stroke treatment [ 24 ], disparities in racial and ethnic representation in stem cell clinical trials [ 25 ], nonpublication rates of registered digital health trials [ 26 ], and relationships between mutations and phenotypes [ 27 ]. With regard to outcomes and other CDEs, Huser et al [ 19 , 20 ] examined the use of CDEs in real data sets and showed how the CDEs identified change by changing the threshold of commonness.…”
Section: Introductionmentioning
confidence: 99%
“…ClinicalTrials.gov data mining has been used to analyze the characteristics of oncology clinical trials [ 8 ], trends in clinical trials for stroke treatment [ 24 ], disparities in racial and ethnic representation in stem cell clinical trials [ 25 ], nonpublication rates of registered digital health trials [ 26 ], and relationships between mutations and phenotypes [ 27 ]. With regard to outcomes and other CDEs, Huser et al [ 19 , 20 ] examined the use of CDEs in real data sets and showed how the CDEs identified change by changing the threshold of commonness.…”
Section: Introductionmentioning
confidence: 99%
“…Even though “ClinicalTrials.gov” is the largest database for clinical trials and represented in more than 200 countries around the globe, a search query in this database does not guarantee completeness. Alternative meta-databases collecting data from even more countries and databases, such as the ICTRP database from the WHO, have not been included in several studies 45 , which implies that some trials may have been missed.…”
Section: Discussionmentioning
confidence: 99%
“…Even though "ClinicalTrials.gov" is the largest database for clinical trials and represented in more than 200 countries around the globe, a search query in this database does not guarantee completeness. Alternative meta-databases collecting data from even more countries and databases, such as the ICTRP database from the WHO, have not been included in several studies (46), which implies that some trials may have been missed.…”
Section: Discussionmentioning
confidence: 99%